Penerapan Metode Design Thinking dan Analisis Kelayakan Finansial Perancangan Alat Pencegah Dehidrasi - Candra, Risfa; Nadia, Citra; Hendrayani, Fitri Adira; Wahidin, Adi Muad; Srimurni, Rafika Ratik (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
Dehydration is a serious medical condition that occurs when the body lacks the fluids necessary to carry out its physiological functions optimally. The problem of dehydration is often overlooked because of its inimmediate nature until it reaches a more severe level. To overcome these problems, a tool is needed that can help individuals to monitor water consumption and remind them to stay hydrated. This research aims to design an Internet of Think (IoT)-based dehydration prevention tool with a Design Thinking approach to ensure that the product is truly useful and accepted by users. The results of the analysis showed that the dehydration prevention device was acceptable if the device was able to remind the user without interfering with daily activities, ergonomic and attractive design, and customizable reminder features. Based on the results of the analysis of the System Usability Scale (SUS) score, this tool obtained a score of 63.67 with a grade scale of D, adjective rating good and included in the Acceptability Ranges category. The results of the financial analysis show that this dehydration prevention tool business is feasible to run. This business has positive indicators such as Net Present Value (NPV) of Rp. Rp. 15,790,933.86, Internal Rate of Return (IRR) of 24%, Benefit/Cost Ratio (B/C Ratio) of 1.21, Payback Period for 2 years and BEP of 43 units per month.   Keywords: Dehydration, Design Thinking, Financial Feasibility Analysis, Tool Design.